Penguatan Program Muslim Friendly Tourism dalam Kegiatan Keagamaan Islam pada Masyarakat Desa Wisata Edukasi Cisaat - Muhamad Ridwan Effendi; Firdaus Wajdi; Rihlah Nur Aulia; Sa'dullah Sa'dullah; Ummu Hani; Adrza Kholwa (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Since Cisaat Village has been designated as an educational tourism village, the Muslim Friendly Tourism development program that has been selected for this service activity has succeeded in showing the identity and socio-religious character of the people of Cisaat Village, also providing strengthening the behaviour of the village community, especially people who become friendly tour attendants according to the teachings and religious beliefs of the people of Cisaat Village and has provided new knowledge insights to the community to be more participate in the potential of religious tourism in their village and provide friendly services that can facilitate tourists when visiting based on the character and local wisdom of Cisaat Village. The five stages of the Community Service activity program of the Assisted Area Assignment Program (P2M-PWBU) are considered effective in achieving the objectives and success indicators of activities that have been determined and have a tangible impact on the sustainability of the Muslim Friendly Tourism program.